Tenant Riskiness, Contract Length, and the Term Structure of Commercial Leases - Jan K. Brueckner; Stuart S. Rosenthal (Center for Economic Studies and ifo Institute (CESifo), 2022)
This paper explores the connection between tenant riskiness, commercial lease length and the term structure of lease contracts. Theory shows that the possibility of default on a long-term lease generates a risk/lease-length connection. The empirical work uses a large CompStak lease dataset combined with tenant characteristics (including risk) from Dun & Bradstreet. Regressions show that lease length is inversely related to the D&B risk measures, as predicted, and that risky tenants pay a higher rent premium for long-term contracts than low-risk tenants. The presence of such tenants thus raises the slope of the term structure of commercial rents.
Keywords: R30; M20; 330; lease length; tenant riskiness; rent term structure